Influence analysis of mobile learning research on modern distance education - Ying Yang; Dan Tian; Ling Wu (2016 2nd IEEE International Conference on Computer and Communications (ICCC), 2016)
Mobile learning is another new learning model after digital learning. It is a new hotspot in the field of educational technology, but also a driver of developing modern distance education. Providing new possibilities for the teaching by applying mobile technology has become a research hotspot in the field of education technology. This article mainly introduced the connotation of mobile learning, analyzed the research status and development trend of mobile learning, and proposed the theoretical significance of mobile learning research on modern distance education.